The Impact of Financial, Non-Financial, and Corporate Governance Attributes on The Practice of Global Reporting Initiative (gri) Based Environmental Disclosure - - Frendy; Indra Wijaya Kusuma (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2011)
Business entities are able to exert their influence on particular stakeholders for the benefit of their interest by managing the information they disseminate to the public, particularly if there is no regulation on such issue in place. Accordingly, the extent of accounting information disclosed to the public, specifically voluntary environmental information, is determined by the internal characteristics of the business entities. The objective of this research is to test the financial, non-financial, and corporate governance attributes of Indonesian public companies which contribute to the extent of environmental information disclosure in Indonesia. This research measured the extent of Indonesian public companies’ environmental disclosure using Environmental Disclosure Index (EDI) as a dependent variable. The index is developed from the parameters under environmental protocols of the Global Reporting Initiative (GRI) G3 framework. Samples of 35 Indonesian public companies are purposively chosen for each of the year from 2005-2008 to form a total of 140 observations.The testing results conclude that size of company, economic performance, and industry sensitivity positively affect environmental disclosure. This research is limited by an assumption that Indonesian public companies employ annual report as the primary means to publicize financial and non-financial information to public.